Collaborative robot zero moment control for direct teaching based on self-measured gravity and friction. (14th November 2018) - Chen, Saixuan; Luo, Minzhou; Jiang, Guanwu; Abdelaziz, Omar
The focus of this study is a moment compensation control algorithm driven by a direct current servo motor. Zero moment robot teaching is achieved with a joint moment compensation algorithm. The moment equilibrium equation is derived based on moment compensation. The current signal detected by a Hall effect sensor is multiplied by a torque constant to estimate the torque value of the robot joint. The compensation current is obtained through parameter identification to overcome gravitational and friction torques. The two variables of speed and position are separately controlled, allowing the compensation current of Coulomb friction and viscous friction force to be separated from the compensation current of friction torque. This study presents the system research, design, and development of a high-precision position control theory of a robot zero moment teaching control method. A collaborative robot is used as the test and verification platform to confirm the feasibility and effectiveness of the proposed theoretical method and implementation technology.